Web-Based Violence Risk Monitoring Tool in Psychoses: Pilot Study in Community Forensic Patients. Issue 1 (1st January 2016) - Gulati, Gautam; Cornish, Robert; Al-Taiar, Hasanen; Miller, Christopher; Khosla, Vivek; Hinds, Christopher; Price, Jonathan; Geddes, John; Fazel, Seena
ABSTRACT: We describe the development and pilot testing of a novel, web-based, violence risk monitoring instrument for use in community patients with psychoses. We describe the development of the tool, including drawing on systematic reviews of the field, how item content was operationalized, the development of a user interface, and its subsequent piloting. Sixty-eight patients were included from three English counties, who had been discharged from forensic psychiatric services. Over 12 months, 310 questionnaires were completed on the sample by professionals from several disciplines and qualitative feedback collected relating to the use of the tool using an electronic survey. Strengths of this approach for risk assessment, and potential limitations and areas for future research, are discussed.